The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1111/j.1365-2605.1980.tb00117.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Steroidogenesis and Hormone Levels in the Epididymis and Vas Deferens of Adult Rats

Abstract: In vivo and in vitro studies with different parts of the epididymis and vas deferens were carried out to determine their inherent capacity to synthesize steroids and to correlate with the endogenous levels with or without the administration of hCG. Incubation with 14C-labelled pregnenolone and testosterone demonstrated that caput epididymidis was more active than other parts in synthesizing testosterone from 14C-pregnenolone and in converting labelled testosterone to 5 alpha-dihydrotestosterone (DHT). The caud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In relation to germ cell development, Tsubota et al (1997) have shown, in the brown bear, that oestradiol plays a role in the reinitiation of spermatogenesis after the beginning of testicular recrudescence (i.e according to seasonal changes) as has been speculated for the squirrel (Pudney et al, 1985). The data of Kumari et al (1980) showing an increase in concentration of oestradiol in the cauda epididymis and vas deferens suggested a possible role for oestrogens in the storage and transport of spermatozoa. All of these observations ®t with the data of Shetty et al (1997) demonstrating that oestrogens play an important role in spermatogenesis and spermiogenesis in the bonnet monkey.…”
Section: Physiological and Pathological Roles Of Oestrogensmentioning
confidence: 92%
See 3 more Smart Citations
“…In relation to germ cell development, Tsubota et al (1997) have shown, in the brown bear, that oestradiol plays a role in the reinitiation of spermatogenesis after the beginning of testicular recrudescence (i.e according to seasonal changes) as has been speculated for the squirrel (Pudney et al, 1985). The data of Kumari et al (1980) showing an increase in concentration of oestradiol in the cauda epididymis and vas deferens suggested a possible role for oestrogens in the storage and transport of spermatozoa. All of these observations ®t with the data of Shetty et al (1997) demonstrating that oestrogens play an important role in spermatogenesis and spermiogenesis in the bonnet monkey.…”
Section: Physiological and Pathological Roles Of Oestrogensmentioning
confidence: 92%
“…injection of hCG increases the urinary concentration of oestrogens whereas castration causes a decrease). Indeed, in rete testis¯uid and in the caput epididymis of the rat, oestrogen concentrations are much higher than in blood (de Jong et al, 1973;Free & Jaffe, 1979;Kumari et al, 1980). Indeed, in rete testis¯uid and in the caput epididymis of the rat, oestrogen concentrations are much higher than in blood (de Jong et al, 1973;Free & Jaffe, 1979;Kumari et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…T was the major steroid in the testis, but its concentration in the epididymis appeared to be markedly reduced ; a significant decrease of T concentration was observed within the epididymis from the efferent ducts to the corpus. A 4 is a precursor of T, and rat and mouse epididymidis can produce T from its precursor (Hamilton, 1971 (Vreeburg, 1975 ;Kumari et al, 1980 ;Nishihara and Suzuki, 1980), rabbit (Frankel and Eik-Nes, 1970), bull and boar (Aafjes and Vreeburg, 1972 ;Ganjam and Amann, 19761 ; …”
Section: Introductionmentioning
confidence: 99%